تأثير نوع العائل النباتي وطريقة التربية على بعض الخصائص الحيوية للأكاروس الأحمر ذو البقعتين Tetranychus urticae Koch 1836 (Acari:Tetranychidae) تحت الظروف المخبرية - صقر, إبراهيم (Latakia University Journal -Biological Sciences Series, 2018)
تم في هذا البحث دراسة تأثير العائل النباتي وطريقة التربية على تطور الأكاروس الأحمر ذي البقعتين وصفاته الحيوية مخبرياً على الفاصولياء والفول والباذنجان والبندورة والخيار وفق طريقتين للتربية (نباتات كاملة- أقراص ورقية) عند حرارة 25±3 ْم ورطوبة نسبية 65 ±5%، وإضاءة مصابيح 12/12 ساعة ضوء/ ظلام. ثبت تفضيل الأكاروس للخيار والفول والفاصولياء على البندورة والباذنجان وبفروق معنوية لدى طريقتي التربية، إذ كانت أقل مدة للتطور الجنيني على الخيار 4.30 و4.40 يوم وسطياً، وأكثرها على الباذنجان 4.77 و 4.87 يوم لدى النباتات والأقراص على التوالي. استغرق التطور من البيضة إلى الحيوان البالغ على الخيار 10.20 و 10.60 وعلى الباذنجان 11.60 و12.00 يوم لدى النباتات والأقراص بالترتيب. كانت خصوبة الإناث أعلى على النباتات وبفروق معنوية عن الأقراص. ومع طريقتي التربية تفوقت الخصوبة على الفاصولياء على باقي العوائل. سُجلت زيادة معنوية في أعداد البيض على العوائل الخمسة في الأيام التي تلت تبديل الأقراص، وكانت الخصوبة أعلى على الأقراص الطرية مقارنةً بالأقراص القديمة. كانت نسبة الفقس أفضل على الأقراص مع تأخير يوم لموعد الخروج الأعظمي لليرقات مقارنةً مع النباتات الكاملة. The effect of the host plant and the raising method on the development of the Tetranychus urticae Koch and its biological characters was studied by using Phaseolus vulgaris L., Vicia faba L., Solanum melogena L., Lycopersicum esculentum Mill and Cucumis sativus as hosts, and adopting two relating methods (Whole plants and leaf disks) under laboratory conditions (25±3 °C, 65±5 %RH and with L12 : D12 h). The results showed C. sativus, V. faba, and P. vulgaris were significantly the preferred hosts for T. urticae whatever the rearing method. The shortest time for embryo-development was recorded on C. sativus as 4.3 and 4.4 days on average, while the longest time was recorded on S. melogena. as 4.77 and 4.87 using the whole plant and leaf disks respectively. The development from egg to adult needed 10.2 and 10.6 days on C. sativus, and 11.6 and 12.0 days on S. melogena using plants and disks respectively. The female fertility on whole plants was significantly higher than on disks. In both methods the fertility on P. vulgaris. was higher than on other hosts. There was a significant increase in the number of eggs on the five hosts immediately following the wetted disks, and fertility was higher on fresh disks compared to old ones. Egg hatching was higher on leaf disks, but with a delay of one for the maximum emergence of larvae compared to whole plants.